2000
DOI: 10.1152/ajpheart.2000.279.2.h657
|View full text |Cite
|
Sign up to set email alerts
|

Estimating oxygen transport resistance of the microvascular wall

Abstract: The problem of diffusion of O(2) across the endothelial surface in precapillary vessels and its utilization in the vascular wall remains unresolved. To establish a relationship between precapillary release of O(2) and vascular wall consumption, we estimated the intravascular flux of O(2) on the basis of published in vivo measurements. To interpret the data, we utilized a diffusion model of the vascular wall and computed possible physiological ranges for O(2) consumption. We found that many flux values were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 76 publications
6
70
0
Order By: Relevance
“…[23]. The average O 2 fluxes from 7 vessels with diameters between 19.5 μm to 35 μm (compiled in [23], original data from [41][42][43][44]) is 4.6 × 10 −5 mlO 2 cm −2 s −1 . The Bi values we considered in this study (1 and 10) provide RBC fluxes which bracket this value, an attempt to describe a range of potential behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]. The average O 2 fluxes from 7 vessels with diameters between 19.5 μm to 35 μm (compiled in [23], original data from [41][42][43][44]) is 4.6 × 10 −5 mlO 2 cm −2 s −1 . The Bi values we considered in this study (1 and 10) provide RBC fluxes which bracket this value, an attempt to describe a range of potential behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have indicated a large amount of O 2 consumption within the microvascular wall, surrounded by a region of lower O 2 consumption [21,22]. These findings are contrasted by a study that reveals the calculated vascular wall O 2 consumption to be much larger than what has been observed in similar tissues [23]. There is no comprehensive model that describes the transport processes in this region.…”
Section: Introductionmentioning
confidence: 91%
“…17 One possible explanation for this is a high oxygen consumption rate of endothelial cells 16,18 ; however, a theoretical study 19 based on a large body of previous reports on endothelial metabolism and oxygen consumption failed to demonstrate a high oxygen disappearance rate from microvessels. Another possibility is overestimation of the oxygen efflux rate related to the assumption on which the estimate of convective oxygen flow was based, ie, the assumption of cross-sectional uniformity of hemoglobin concentration and SO 2 within microvessels, 11 especially because intravascular SO 2 is inhomogeneously distributed, with a high centerline level and low level near the vessel wall, as shown by Mott et al 12 and in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…While many researchers are conducting oxygen transport studies in cells cultured under unitg conditions (e.g., Vadapalli et al, 2000), little information is available on responses of oxygen-dependent cellular processes under micro-g. The PC12 cell line and its molecular machinery is well characterized in its response to oxygen (both high and low oxygen environments), and thus this cell line is a useful model for studying the oxygen-sensitive molecular and cellular mechanisms (Greene and Tischler, 1976;Czyzyk-Krzeska et al, 1994;Kumar et al, 1998).…”
Section: Introductionmentioning
confidence: 99%